ANALISIS KONDISI RESERVOIR PANAS BUMI DENGAN MENGGUNAKAN DATA GEOKIMIA DAN MONITORING PRODUKSI SUMUR ELS-02 LAPANGAN ELSA - Nabilla Elsaphira Putri; Onnie Ridaliani; Widia Yanti (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2019)
A good reservoir management is needed to maintain the availability and quality of geothermal production fluid. When producing geothermal fluids, there are some changes in reservoir parameters such as declining of reservoir pressure and temperature, chemical composition of geothermal fluids, and states of fluid that would affect the quality of reservoir by mixing, boiling, or cooling processes that may be happened because of those changes. It is becoming a concern on reservoir management. In this case, chemical concentrations of fluids monitoring is one of methods that can perform to reach a well reservoir management of geothermal field. With chemical monitoring process, current reservoir condition and processes that occurred during exploitation can be defined. In ELS-02 by monitoring and analyzing its enthalpy changes, chloride concentration changes, and NCG concentration changes and supported by its calcium, sulphate, and carbonate concentration profile, two processes could be defined: mixing with surface cooler water and reinjection breakthrough. Other than that, casing leak that causing surface water enter the well could be detected.  These become a sign to reservoir engineer to prepare for problems that may occur in near time term relating to well problem such as scaling and long time problem like massive cooling or drying of reservoir. After all, further development scenario of Elsa field can be made to improve its performance in producing fluids and heats.